Sex differences between women and men with COPD: A new analysis of the 3CIA study. (September 2020) - Perez, Tamara Alonso; Castillo, Elena García; Ancochea, Julio; Pastor Sanz, María Teresa; Almagro, Pere; Martínez-Camblor, Pablo; Miravitlles, Marc; Rodríguez-Carballeira, Mónica; Navarro, Annie; Lamprecht, Bernd; Ramírez-García Luna, Ana S.; Kaiser, Bernhard; et al.
Abstract : Background: There is partial evidence that COPD is expressed differently in women than in men, namely on symptoms, pulmonary function, exacerbations, comorbidities or prognosis. There is a need to improve the characterization of COPD in females. Methods: We obtained and pooled data of 17 139 patients from 22 COPD cohorts and analysed the clinical differences by sex, establishing the relationship between these characteristics in women and the prognosis and severity of the disease. Comparisons were established with standard statistics and survival analysis, including crude and multivariate Cox-regression analysis. Results: Overall, 5355 (31.2%) women were compared with men with COPD. Women were younger, had lower pack-years, greater FEV1 %, lower BMI and a greater number of exacerbations (all p < 0.05). On symptoms, women reported more dyspnea, equal cough but less expectoration (p < 0.001). There were no differences in the BODE index score in women (2.4) versus men (2.4) (p = 0.5), but the distribution of all BODE components was highly variable by sex within different thresholds of BODE. On prognosis, 5-year survival was higher in COPD females (86.9%) than in males (76.3%), p < 0.001, in all patients and within each of the specific comorbidities that we assessed. The crude and adjusted RR and 95% C.I. for death in males was 1.82 (1.69–1.96) and 1.73 (1.50–2.00), respectively. Conclusions: COPD in women has some characteristic traits expressed differently than compared to men, mainly with more dyspnea and COPD exacerbations and less phlegm, among others, although long-term survival appears better in female COPD patients. Highlights: There are sex-related differences in COPD risk and outcomes. Women with COPD are younger, less smokers, had better lung function, but experienced more dyspnea and exacerbations. Our data suggest that the proportional weight of each of the components of the BODE index varied by sex. Women with COPD had better survival tan men.